2011
DOI: 10.1016/j.ajhg.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Human Mutations in NDE1 Cause Extreme Microcephaly with Lissencephaly

Abstract: In the original version of this article, the title was incorrectly written as ''Human Mutations in the NDE1 Cause Extreme Microcephaly with Lissencephaly.'' This error has been corrected in both the online and the print version. The journal regrets the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…48 103 Among them, the nuclear distribution gene E homologue 1 ( NDE1 ) is of particular interest, because the nudE neurodevelopment protein 1 is essential for mitosis and neurodevelopment, and interacts with the disrupted in SZ 1 protein,105 implicated in SZ and in other major psychiatric disorders 106–108 . NDE1 deficiency impairs neurogenesis, by causing profound neuronal proliferation defects and a deficiency in cortical lamination, as observed in Nde1-null mice and in patients with NDE1 homozygous mutations, who present extreme microcephaly with lissencephaly 106 107. Severe microcephaly, including fetal brain disruption, can also be caused by the combination of a 16p13.11del and a mutation on the non-deleted NDE1 homologue 108.…”
Section: Recurrent Cnvs Associated With Increased Risk For Ndsmentioning
confidence: 98%
“…48 103 Among them, the nuclear distribution gene E homologue 1 ( NDE1 ) is of particular interest, because the nudE neurodevelopment protein 1 is essential for mitosis and neurodevelopment, and interacts with the disrupted in SZ 1 protein,105 implicated in SZ and in other major psychiatric disorders 106–108 . NDE1 deficiency impairs neurogenesis, by causing profound neuronal proliferation defects and a deficiency in cortical lamination, as observed in Nde1-null mice and in patients with NDE1 homozygous mutations, who present extreme microcephaly with lissencephaly 106 107. Severe microcephaly, including fetal brain disruption, can also be caused by the combination of a 16p13.11del and a mutation on the non-deleted NDE1 homologue 108.…”
Section: Recurrent Cnvs Associated With Increased Risk For Ndsmentioning
confidence: 98%
“…Two major regulatory complexes are dynactin and NudE‐ or NudE‐LIS1, which act via the dynein intermediate chain [Vallee et al., ]. Mutations in NudE, NudEL, and LIS1 cause alterations in mouse, rat, and human brain development, leading to microcephaly and lissencephaly [Dobyns et al., ; Feng et al., ; Sasaki et al., ; Tsai et al., 2005; Alkuraya et al., ]. In contrast, mutations in dynactin result in various motor neuron diseases including amyotrophic lateral sclerosis and hereditary motor neuropathy type VIIB (HMNVIIB) [Puls et al., ].…”
mentioning
confidence: 99%
“…Unlike in lissencephaly, microcephaly is characterized by reduced brain size and mental retardation. Bakircioglu et al [79] and Alkuraya et al [80] found distinct homozygous frameshift mutations in NDE1 and showed that the truncated mutant proteins failed to bind to the dynein complex. Bakircioglu et al [79] and Alkuraya et al [80] found distinct homozygous frameshift mutations in NDE1 and showed that the truncated mutant proteins failed to bind to the dynein complex.…”
Section: Mutations In Lis-1 and Nde1mentioning
confidence: 99%
“…Bakircioglu et al [79] and Alkuraya et al [80] found distinct homozygous frameshift mutations in NDE1 and showed that the truncated mutant proteins failed to bind to the dynein complex. Depletion of the Nde1 gene in mice leads to a small brain, mental retardation and mild neuronal migration defects [80]. Depletion of the Nde1 gene in mice leads to a small brain, mental retardation and mild neuronal migration defects [80].…”
Section: Mutations In Lis-1 and Nde1mentioning
confidence: 99%